The Use of Small Capital Selling Snacks as A Business Opportunity in The Langowan Shopping Complex - Sumampouw, Olviane Olke (AIBPM Publisher, 2021)
Langowan is a strategic center of economic activity because it is a meeting place for several sub-districts in Minahasa and Mitra. Therefore, the authors see a market opportunity to start a business selling snacks, including selling wet and dry cakes in the Langowan shopping complex. By considering the research objectives that have been set, this research tends to use the